2009
DOI: 10.1053/j.gastro.2009.02.062
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Utility Analysis of Ablative Therapy for Barrett's Esophagus

Abstract: Background & Aims Recommendations for patients with Barrett’s esophagus (BE) include endoscopic surveillance with esophagectomy for early-stage cancer, although new technologies to ablate dysplasia and metaplasia are available. This study compares the cost-utility of ablation with that of endoscopic surveillance strategies. Methods A decision analysis model was created to examine a population of patients with BE (mean age 50), with separate analyses for patients with no dysplasia, low-grade dysplasia (LGD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 119 publications
3
133
1
3
Order By: Relevance
“…Three studies were identified that reported transition probabilities [25][26][27]. Many of the inputs reported were the same or similar.…”
Section: Model Inputs Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies were identified that reported transition probabilities [25][26][27]. Many of the inputs reported were the same or similar.…”
Section: Model Inputs Effectivenessmentioning
confidence: 99%
“…However, these data were mostly taken from Shaheen et al [25] which is considered separately. Therefore, the options included in the model were two sets of probabilities from Inadomi et al [26] and one from Shaheen et al [25]. Inadomi et al was selected for the base case input because this was the most up-to-date.…”
Section: Model Inputs Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been a particularly contentious topic with health economic studies producing mixed results as to the cost-effectiveness of endoscopic surveillance of Barrett's esophagus [5]. In 2009 two US studies recorded mean costs per patient under surveillance of $2,769 [31] and $11,532 [32] for surveillance programs involving 5-yearly screening intervals, and $7,940 was reported for one UK study with 3-yearly intervals (converted to $ 2009) [13]. Our cost cut-off of $4971 per patient within an early detection program appears to be in the overall range of these costs.…”
Section: Discussionmentioning
confidence: 99%